Reboot-based Recovery of Performance Anomalies in Adaptive Bitrate Video-Streaming Services - Cunha, Carlos Augusto da Silva (2016)
Performance anomalies represent one common type of failures in Internet servers. Overcoming these failures without introducing server downtimes is of the utmost importance in video-streaming services. These services have large user abandon- ment costs when failures occur after users watch a significant part of a video. Reboot is the most popular and effective technique for overcoming performance anomalies but it takes several minutes from start until the server is warmed-up again to run at its full capacity. During that period, the server is unavailable or provides limited capacity to process end-users’ requests. This paper presents a recovery technique for performance anomalies in HTTP Streaming services, which relies on Container-based Virtualization to implement an efficient multi-phase server reboot technique that minimizes the service downtime. The recovery process includes analysis of variance of request-response times to delimit the server warm-up period, after which the server is running at its full capacity. Experimental results show that the Virtual Container recovery process completes in 72 seconds, which contrasts with the 434 seconds required for full operating system recovery. Both recovery types generate service downtimes imperceptible to end-users.